Microbial diversity in drug-naïve Parkinson’s disease patients - Eliša Papić; Valentino Rački; Mario Hero; Ana Nyasha Zimani; Mojca Čižek Sajko; Gloria Rožmarić; Nada Starčević Čizmarević; Saša Ostojić; Miljenko Kapović; Goran Hauser; Aleš Maver; Borut Peterlin; et al. (PLoS ONE, 2025)
Parkinson’s disease (PD) is a neurological disorder characterized by rigidity, bradykinesia and tremor. Several genetic and environmental causes of PD are known, and there is emerging evidence of the possible contribution of the gut microbiome to the disease onset, severity, and response to therapy. While previous research has shown several differences in the microbiome of PD patients under therapy as opposed to healthy controls, few prospective studies have included drug-naïve patients. In order to evaluate the gut microbiome composition prior to therapy initiation, we collected and performed 16S rRNA gene sequencing of the stool samples from 49 drug-naïve PD patients and compared them to 34 diet and lifestyle-matched controls from the Croatian population (GiOPARK Project). While no significant alpha diversity difference was observed between the patients and controls, the differential relative abundance analysis showed an increase in Bacteroides fluxus, B. interstinalis, B. eggerthii, and Dielma fastidiosa in the drug-naïve PD patients compared to controls, while Alistipes, Barnesiella and Dialister spp. were decreased in patients compared to controls. Despite preserved overall diversity, these changes may indicate early microbial dysbiosis and represent a foundation for future studies exploring microbiome changes across disease progression and treatment.